Ecology and Ethnomycological Study of Some Wild Mushrooms in Tropical Riverine Forest, Lumbini Province, West Nepal - Bhattarai, Anand Prasad; Adhikari, Hari Sharan; Aryal, Hari Prasad; Budhathoki, Usha (Amrit Research Journal, 2024)
Mushrooms are an integral part of the forest ecosystem. The forest’s tree species diversity and humid environment during the monsoon period favor the ideal growth of a diverse group of mushrooms. A study was conducted in a tropical riverine forest named Sukhaura Hariyali Community Forest at Makrahar, Rupandehi, Lumbini province, to investigate the diversity of ethnomycological use of wild mushrooms. An opportunistic sampling method was used for the collection of wild mushroom samples. Thirty-three specimens of wild mushrooms were collected, and twenty-three species from sixteen genera belonging to twelve families were identified. The ethnomycological significance of collected species was also explored from the study sites. Among the surveyed species, Russula (five species) was the most widely distributed in the studied area. The ecological preference of the species revealed that a maximum of twelve species were mycorrhizal, ten species were found saprophytic, and a single species (Fomes fomentarius) was found parasitic. Ten species were found to be edible, while poisonous and inedible mushrooms comprise three and seven species respectively. Agaricus arvensis, Pycnoporus cinnabarinus, and Xerocomus subtomentosus, were found to be used by locals for therapeutic purposes. The study provides the baseline data for macrofungal diversity, ecology, wild mushroom exploration, and their use.